Risk Factors for the Development of Silicone Oil Induced Glaucoma: A Retrospective Analysis - T. N. Yurieva; I. M. Koniaeva; I. M. Mihalevich; L. I. Davidova (Oftalʹmologiâ)
Background. Performing a three-port vitrectomy with the adjunction of silicone oil (SO) for internal tamponade is the most common surgery in the treatment of complicated pathology of the posterior eye segment. A possible complication of this surgery is the development of secondary silicone oil induced glaucoma (SIG).Methods. This article presents a retrospective analysis of the medical histories of 400 patients who underwent vitrectomy with SO adjunction and its subsequent removal, analysis of the patient’s anatomical and functional data, and determination of the risk factors for SIG development. A review of the literature was also conducted, aimed to identify SIG risk factors, and the data of the retrospective analysis were compared with global data.Results. SIG was established in 56 (14%) of 400 patients within 1 to 34 months after vitrectomy. The most significant risk factor for the development of SIG is the duration of tamponade of the vitreal cavity with SO. Also, according to our data, the likelihood of SIG increases in eyes after IOL implantation and in patients with aphakia, in myopic patients, as well as in males and in younger patients. These data are consistent with global trends. There was no increase in the risk of SIG depending on the nosology that led to vitrectomy, the presence of diabetes mellitus, which is also confirmed in the literature. The difference was in growth of SIG risk in patients after scleral buckling (according to the literature, the risk has to be reduced).Conclusion. Further investigation of the problem of SIG and risk factors understanding will enhance the visual prognosis after surgery and improve the quality of patient’s life.